Diet energy density and time on feed effects on beef longissimus muscle palatability - Burson, D.E.; Hunt, Melvin C.; Allen, Dell M.; Kastner, Curtis L.; Kropf, Donald H. (American Society of Animal Science, 2008)
To evaluate the combined effects of time on feed and diet energy density on the palatability of beef longissimus muscle steaks, we randomly allotted 112 Angus yearling steers to 14 nutritional regimens (eight steers per treatment): control group (C), submaintenance group (S) and 12 groups fed either a low (L), medium (M) or high (H) energy density diet (.771, .992 or 1.28 Meal NEp/kg, respectively) and slaughtered after 56, 91, 119, 147 (M and H groups only) or 175 (H group only) days on feed. Taste panel evaluations, lnstron textural assessments and sarcomere length measurements were conducted on longissimus muscle samples collected 7 days postmortem. Taste panel muscle fiber tenderness, overall tenderness, juiciness and flavor intensity scores were not influenced (P>.05) by nutritional regimen. Connective tissue was most detectable in steaks from the S group, but the amount was similar (P>.05) to that detected in the C, L-56 and H-147 groups' steaks. In general, steaks from cattle fed L diets for 91 or more days or M or H diets for 56 or more days had the least amount of detectable connective tissue. Values for peak force and peak force minus initial-yield force were affected (P<.05) by nutritional regimen; however, there was no consistent pattern for these variables. Steaks from cattle in the S group had the shortest longissimus muscle sarcomere lengths (1.73/am). C group sarcomere lengths were shorter than those of all L, M and H diet groups except M-56, but these differences did not affect measurements of muscle fiber tenderness.
Keywords: Food science; Nutritional regimen; Diet energy density; Time on feed; Palatability; Tenderness; Beef